PENGARUH CR, DER, ROA DAN TATO TERHADAP EARNING PER SHARE PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA - Ferico; Novianty; Yunita Sigalingging; Tasya Monica; Enda Noviyanti Simorangkir (Sekolah Menengah Kejuruan (SMK) Pustek, 2021)
This study aims to examine the effect of CR, DER, ROA and TATO on Earning per Share of manufacturing companies on the Indonesia Stock Exchange (BEI) for the period 2017-2019. The phenomenon that occurs is an increase in CR, DER, ROA and TATO is not followed by an increase in Earnings Per Share manufacturing companies on the IDX for the 2017-2019 period are the background for this research. The sample technique used is the method purpose sampling. Samples were taken totaling 198 analyzes. The results showed that CR, DER and TATO partially had no effect on the Earnings Per Share of manufacturing companies on the IDX for the 2017-2019 period. ROA partially affected the Earnings Per Share of manufacturing companies on the IDX for the period 2017 - 2019. CR, DER, ROA and TATO simultaneously influences the Earnings Per Share of manufacturing companies on the IDX for the period 2017 - 2019.